WHAT ARE THE CHARACTERISTICS OF A GOOD ASSESSMENT IN COUNSELING? - Rahmi Dwi Febriani; A. Muri Yusuf; Daharnis Daharnis (Widyagogik, 2022)
Assessment is very important in counseling. Assessment in counseling is an assessment activity carried out by the counselor, as well as the counselee condition which is revealed through the assessment process. Results obtained from assessment be one base used for formulate guidance and counseling programs. The purpose of the assessment is to obtain relevant, objective, and comprehensive data regarding the condition of students. Remember importance a assessment that, moreover used as tool taker decision, of course required good assessment characteristics.